WOMEN’S LEADERSHIP IN ISLAMIC EDUCATIONAL INSTITUTIONS: LEADERSHIP STYLES, CHALLENGES, AND ADAPTIVE STRATEGIES OF A FEMALE MADRASAH PRINCIPAL - Kristi Wulandari (STKIP Pesisir Selatan, 2026)
This study aims to analyze women’s leadership in Islamic educational institutions by examining leadership styles, challenges, and strategies employed by a female madrasah principal at MTs Negeri 4 Kota Jambi. This research adopts a qualitative approach using a case study design, with data collected through interviews, observations, and documentation. The study reflects the growing recognition of women’s roles in educational leadership, particularly within contexts that have traditionally been dominated by men. The findings reveal that the principal applies participatory, transformational, and relational leadership styles that foster collaboration, open communication, and improved teacher performance. These leadership approaches contribute to the development of a supportive and productive organizational environment. Despite these contributions, the principal faces several challenges, including gender stereotypes, socio-cultural expectations, and institutional constraints such as limited resources and administrative demands. These challenges require not only managerial skills but also adaptability in navigating complex organizational dynamics. To address these challenges, the principal employs adaptive strategies that emphasize professionalism, competence, effective communication, and value-based leadership grounded in Islamic principles. These strategies strengthen her leadership effectiveness and reinforce her legitimacy within the institution.